Description of the adult male of Aeschnosoma auripennis Geijskes, 1970 (Odonata: Corduliidae s.s.) - Neiss, Ulisses Gaspar; Fleck, Günther; Feitoza, Lorrane Aesha Malta; Hamada, Neusa (Zootaxa, 2013)
The male of Aeschnosoma auripennis is described for the first time, based on a specimen reared from a larva collected in the Reserva Biológica do Uatumã, Amazonas State, Brazil. The species is newly reported from the Roraima State, Brazil.